2020
DOI: 10.1101/2020.03.03.970251
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kinome Profiling of Primary Endometrial Tumors Using Multiplexed Inhibitor Beads and Mass Spectrometry Identifies SRPK1 As Candidate Therapeutic Target

Abstract: Protein kinases (collectively, termed the kinome) represent one of the most tractable drug targets in the pursuit of new and effective cancer treatments. However, less than 20% of the kinome is currently being explored as primary targets for cancer therapy, leaving the majority of the kinome untargeted for drug therapy. Chemical proteomics approaches such as Multiplexed Inhibitor Beads and Mass Spectrometry (MIB-MS) have been developed that measure the

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…In this work, using MIB-MS (19,20), we explored a high percentage (296/518) of the human kinome in treatment naïve primary GIST specimens from three GIST subtypes (KIT-mutant, PDGFRA-mutant and SDH-d GIST) in order to identify potential novel targets. Using this proteomics approach, we demonstrated that the three GIST subtypes have distinct kinome profiles, and identified kinases that are universally overexpressed in all GIST, as well as kinases that are unique to each subtype.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, using MIB-MS (19,20), we explored a high percentage (296/518) of the human kinome in treatment naïve primary GIST specimens from three GIST subtypes (KIT-mutant, PDGFRA-mutant and SDH-d GIST) in order to identify potential novel targets. Using this proteomics approach, we demonstrated that the three GIST subtypes have distinct kinome profiles, and identified kinases that are universally overexpressed in all GIST, as well as kinases that are unique to each subtype.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, using MIB-MS (19,20), we explored the majority of the kinome in treatment naïve primary GIST specimens from three GIST subtypes (KIT-mutant, PDGFRA-mutant and SDH-d GIST) in order to identify potential novel targets. Using this proteomics approach, we demonstrated that the three GIST subtypes have distinct kinome profiles, and identified kinases that are universally activated in all GIST, as well as kinases that are unique to each subtype.…”
Section: Introductionmentioning
confidence: 99%